WORLD-CLASS NEW TECHNOLOGIES IN THE TREATMENT OF URINARY DISEASES (World Bulletin of Public Health, 2022)
Since prehistoric times, our understanding of urology has rapidly expanded. Whilst primitive urologists began by using urine as a therapeutic substance, modern urologists may find themselves removing a kidney remotely by driving a robotic arm, with seven degrees of movement, while using image overlay-augmented reality. This review provides an insight into the potential status of urological technology in 20 years’ time, assessed through an analysis of developments in imaging, diagnostics, robotics and further technologies. A particular emphasis is given to the promising fields of minimally invasive techniques, nanotechnology and tissue engineering, which likely hold the key to a new era for urology
Keywords: Diagnostic tools; future technology; imaging; robotics